2019
DOI: 10.29399/npa.23505
|View full text |Cite
|
Sign up to set email alerts
|

HBsAg, anti-HCV and anti-HIV seroprevalance among drug users : A retrospective assessment

Abstract: Introduction: Drug abuse and co-occurring infections are associated with significant morbidity and mortality. In regions with high rates of drug usage, infections like hepatitis B virus (HBV), hepatitis C virus (HCV) and human immunodeficiency virus (HIV) are highly prevalent. Epidemiological studies on HBV, HCV and HIV infections among users of illicit drugs are scarce in Turkey. The primary aim of this cross-sectional and retrospective study was to determine the hepatitis B surface antigen (HBsAg), anti-HCV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…It was reported that 3 (17.6%) of these patients were anti-HCV positive and 1 (5.8%) was anti-HIV positive. No HBsAg positivity was detected in the same patient group (24). Similarly, our study found a mean age of intravenous substance use of 29.90±7.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…It was reported that 3 (17.6%) of these patients were anti-HCV positive and 1 (5.8%) was anti-HIV positive. No HBsAg positivity was detected in the same patient group (24). Similarly, our study found a mean age of intravenous substance use of 29.90±7.…”
Section: Discussionsupporting
confidence: 76%
“…with HBsAg positivity and 1 patient (1.9%) with anti-HCV positivity were detected whereas no patients with anti-HIV positivity were detected (23). Another study has reported that out of 4357 patients that consists mostly of non-intravenous substance users 94 (2.2%) were HBsAg positive; out of 4451 patients 27 (0.6%) were anti-HCV positive; and out of 4464 patients 10 (0.2%) were anti-HIV positive (24). Different studies have given anti-HCV positivity rates in cannabis users as 0% (19), 1.8% (18), 1.8% (25), and 0.6% (24).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…50.9% of HBsAg-positive subjects were females and the mean age was 40:8 ± 14:7 years [115]. Interestingly, screening of drug abusers between January 2013 and December 2017 demonstrated the existence of HBsAg in 94 out of 4357 patients (2.2%), aging between 14 and 71 years [116]. The prevalence of HBV genotypes in Turkey was screened from February 2001 to February 2002 on 158 patients (99 males and 59 females).…”
Section: Preventionmentioning
confidence: 99%
“…44 Similar finding was obtained later by other studies too. 45 In this context, one study from Saudi Arabia found distinct advantage of antigen-antibody combined ELISA in detecting HCV amongst PWID population with higher detection rate than antibody ELISA and comparable result with RNA detection method. 46 In PWIDs from resource-limited African setting, antigen detection method was found to be with comparable result with RNA detection in contrast to antibody detection.…”
Section: Discussionmentioning
confidence: 98%